The effects of predator odor (TMT) exposure and mGlu3 NAM pretreatment on behavioral and NMDA receptor adaptations in the brain. (1st April 2022) - Tyler, Ryan E.; Bluitt, Maya N.; Engers, Julie L.; Lindsley, Craig W.; Besheer, Joyce
Abstract: A stressor can trigger lasting adaptations that contribute to neuropsychiatric disorders. Predator odor (TMT) exposure is an innate stressor that may activate the metabotropic glutamate receptor 3 (mGlu3 ) to produce stress adaptations. To evaluate functional involvement, the mGlu3 negative allosteric modulator (NAM, VU6010572; 3 mg/kg, i.p.) was administered before TMT exposure in male, Long Evans rats. Two weeks after, rats underwent context re-exposure, elevated zero maze (ZM), and acoustic startle (ASR) behavioral tests, followed by RT-PCR gene expression in the insular cortex and bed nucleus of the stria terminalis (BNST) to evaluate lasting behavioral and molecular adaptations from the stressor. Rats displayed stress-reactive behaviors in response to TMT exposure that were not affected by VU6010572. Freezing and hyperactivity were observed during the context re-exposure, and mGlu3 -NAM pretreatment during stressor prevented the context freezing response. TMT exposure did not affect ZM or ASR measures, but VU6010572 increased time spent in the open arms of the ZM and ASR habituation regardless of stressor treatment. In the insular cortex, TMT exposure increased expression of mGlu ( Grm3, Grm5 ) and NMDA ( GriN2A, GriN2B, GriN2C, GriN3A, GriN3B ) receptor transcripts, and mGlu3 -NAM pretreatment blocked GriN3B upregulation. In the BNST, TMT exposure increased expression of GriN2B and GriN3B in vehicle-treated rats, but decreased expression in the mGlu3 -NAM group. Similar to the insular cortex, mGlu3 -NAM reversed the stressor-induced upregulation of GriN3B in the BNST. mGlu3 -NAM also upregulated GriN2A, GriN2B, GriN3B and Grm2 in the control group, but not the TMT group. Together, these data implicate mGlu3 receptor signaling in some lasting adaptations of predator odor stressor and anxiolytic-like effects. Highlights: mGlu3 -NAM pretreatment does not affect TMT exposure stress-reactive behaviors. TMT exposure produces freezing and hyperactivity in response to the TMT-paired context. mGlu3 -NAM pretreatment prevents freezing response to the context. mGlu3 -NAM pretreatment produces lasting anxiolytic-like effects. TMT exposure and mGlu3 -NAM affect glutamatergic gene expression in the insular cortex and BNST.